An Assessment of Vertically Integrated Contract Poultry Farming: A Case Study in Bangladesh - Begum, Ismat Ara (International Journal of Poultry Science, 2005)
The present study was undertaken to identify incentives for poultry farmers to participate in contract farming system in Bangladesh. This paper explores the causes why the farmer entering into contract farming system and evaluates the performance of vertically integrated contract poultry farming system on farmer`s income by analyzing the cost and returns and labor utilization. Poultry meat is the most widely accepted meat in Bangladesh. Although Government provide various favourable policies for poultry sector development but still now meat deficiency is 89.5%.This is largely because the necessary backward and forward market linkages are rarely in place, i.e. rural farmers and small scale entrepreneurs lack both reliable and cost efficient inputs, credit for running business and guaranteed and profitable markets for their output. Vertically integrated contract farming could be one possible solution in this situation. With effective management, vertically integrated contract farming system can be a means to develop markets and to bring about the transfer of technical skill in a way that is profitable for both farmers and integrators. This study was based on the primary data collected from 50 sample farm of ABFL, the pioneer vertically integrated poultry contract firm, kishorganj in Bangladesh. It was revealed in the study that contract farmers get several incentives from vertically integrated firm such as credit, production and price risk reduction, marketing assistance, technical know-how etc. The study also found that the contract farmers were better off in their net income by getting the high net return from the poultry farm.